Globalisation and Nature Policy: An Integrated Environmental-Economic Framework - C. Martijn van der Heide; Jeroen C.J.M. van den Bergh; Ekko C. van Ierland (Tinbergen Institute, 1999)
The search for a framework to study globalisation, economics and ecology for nature conservation andbiodiversity protection requires the integration of concepts, theories and models from economics andecology. This allows for the study of interactions between economic and ecological processes, includingprotection of species and biodiversity, sustainable and optimal use of renewable resources, land use andphysical planning, maintenance of nature areas, acquisition of nature areas, and development of outdoorrecreation areas. Economic theories relating to nature and ecosystems have focused on notions of capitaltheory and intertemporal trade-offs, decision making under uncertainty and irreversibility, and marginalvaluation and cost-benefit analysis. Recently, the conservation and valuation of biodiversity, and theresilience of ecological and combined ecological-economic systems, have attracted a great deal of attentionin the environmental and resource economics literature. In addition, the distinction between local and globalcosts and benefits of environmental and biodiversity policies is regarded to have significant impacts oninternational co-operation.Ecology can be incorporated in economic analyses in various ways, notably by offering informationabout the hierarchy of dynamic ecological processes, including population dynamics, ecosystem successionand cycles, and long run trends of selection and evolution. Biodiversity has been linked to resilience in theanalysis of complex ecological-economic systems. Understanding of ecosystem irreversibility anduncertainty can improve economic analysis of decisions with impacts on ecosystem. Ecosystemperformance indicators, such as those proposed around the concept of ecosystem health, can be useful formultidisciplinary modelling and evaluation studies. Finally, monetary valuation studies of goods and servicesprovided by ecosystems can be complemented by detailed information about ecosystem scenarios andfunctions.The paper discusses existing approaches to integrate economics and ecology, reviews the mostimportant studies found in the literature, and suggests a number of general frameworks and models toaddress pressing policy questions relating to globalisation, conservation of biodiversity, sustainable use ofnatural resources, and sustainable land use.
Keywords: 330; Globalisierung; Naturschutz; Welt